Comparison of Four Different Methods for the Recovery of Dotriacontane-16,17-14C from Small Animal Respiratory Tissue - Kmoch, N.; Reznik, G.; Haindl, H.; Mohr, U. (Nuklearmedizin - NuclearMedicine, 1975)
The efficiency and accuracy of four different methods of tissue preparation for the recovery of dotriacontane-16,17-14C (DOT-16,17-14C) from rat respiratory tissue were compared by means of liquid scintillation counting. A DOT-16, 17-14C standard solution was placed on the respiratory epithelium of the nasal apex, larynx, trachea and main bronchi. Combustion of the lyophilized organs in a Packard sample oxidizer revealed the highest recovery and accuracy (93—100%), sample oxidizing by combustion without lyophilization the lowest recovery and accuracy (73—92%). Tissue solubilization by the commercially available tissue solubilizer TS-1 revealed a better recovery and accuracy (89—95%) than tissue maceration by boiling in methanolic KOH and toluene extraction (74—91%). Depending on the laboratory equipment, lyophilization or tissue solubilization is preferred; maceration and toluene extraction as well as combustion without freeze-drying are disregarded for further investigations because of the cumbersome procedure as well as the low recovery and accuracy, respectively.